(untitled) (Educational Perspectives Magazine (REPED), 2023)
The next research is interpretative and it is leaded to show the knowledge the students of Biology and Natural Sciences Education Programme develops from the use of blogs as a place to register systematic observations and reflections. This experience is set in a progressive teaching training context, having as theoretical references, the relationship between formal and practical knowledge, as well as reflexive levels. A qualitative analysis was developed. The knowledge about certain moments in a class and the types of rational thoughts, which are present in reflexive processes of the students are taken to be analysed. The way towards interpretative rationality and previous teaching reflexive experiences are taken into account. On the other hand, the knowledge about practice plays a very important role, since it leads to a transformation of students’ beliefs and it encourages reflexive processes. Thus, furthermore, an early construction of their own representation as a professional able to find solution to real problems, to think about them, making the best decisions for the school context.